Comparative Analysis of Steam and Epic Games Store Application Satisfaction Levels Using the Pieces Method - Kusumarini, Cahyawati Diah; Ansi, Caesario Dwinathaly (Lentera Ilmu Nusantara, 2025)
Application-based game stores are on the rise recently, so there is a tight gap between Steam and the Epic Games Store. This research provided a description of user satisfaction level towards the two applications and served as a measure of the success of these two applications. The type of research conducted was quantitative research that analyzes data collection from a Likert scale questionnaire instrument. The method used was a descriptive analysis of user satisfaction level on both applications using the PIECES method. This research showed that both applications get satisfaction level results of